Literatura doby staropolskiej w wypowiedziach Jana Pawła II wygłoszonych podczas pielgrzymek do Polski = The literature of an old polish period in statements of John Paul 2nd during his pilgrimages to Poland - Seul, Anastazja (1961- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author of an article` Literature of an old polish period in statements of John Paul 2nd during hispilgrimages to Poland` shows that Pope refers to those authors and literature masterpieces whichformed the spirit of a Polish nation and helped Poles to survive and keep a national identity inmost difficult stages of their history.
Keywords: Jan Paweł II, papież (1929-2005); mowy i homilie; literatura polska - historia - 10-16 w.